Recent Advancements in Healthcare Digitalization: A Literature Review - Tourkakis, George; Chatzipetrou, Evrikleia (International Conference on Business and Economics - Hellenic Open University, 2025)
This paper investigates the recent advancements in healthcare, taking into account the new possibilities of the new technologies, personalized medicine and the impact that they have on global health. It explores the way through which advanced technologies, such as blockchain technology, the Artificial Intelligence (AI), and the Augmented Reality/Virtual Reality (AR/VR) systems, offer transformation in healthcare delivery. It also explores the main elements of digitalizing healthcare, such as Electronic Helath Records (EHRs), Telemedicine, m Health, AI and Machine Learning (ML) technological systems and Internet of Medical Things (IoMT). These technologies are able to enhance data security, diagnostic accuracy and medical training, while improving the efficiency of administrative tasks. Moreover, the paper presents the benefits of personalized medicine, by emphasizing the significance of genomics and individualized treatment plans that offer targeted therapies, genetic screening and precision medicine. JEL Classifications: C31, C50, I10, I19 Keywords: Digitalization, Healthcare, Electronic Health Records (EHRs), Mobile Health (mHealth), Artificial Intelligence (AI) and Machine Learning (ML)